Intelligent Transport Systems and Pedestrian Traffic - Šimunović, Ljupko; Bošnjak, Ivan; Mandžuka, Sadko (Promet - Traffic&Transportation, 2012)
The paper gives an overview of the past development and implementation of Intelligent Transport Systems in pedestrian traffic. Starting from recent development projects and methodological approaches to the development of ITS, an overview of the existing technologies of implementing ITS in pedestrian traffic is given, and some solutions are proposed that would be feasible in the Republic of Croatia, as well as in other transition countries. As the most significant functions of integrated systems within ITS, the possibilities are presented of locating pedestrians in the network, pedestrian guidance (especially the blind and low-vision persons as well as persons in wheelchairs), provision of on-trip information, etc. Special focus is on the area of pedestrian protection in traffic (avoidance of accidents) using devices fitted onboard vehicles and embedded in road infrastructure. The significance of timely integration of the pedestrian traffic in designing the future ITS architecture has been indicated.KEY WORDS: intelligent transport systems (ITS), pedestrian traffic, pedestrian guidance, real-time information, traffic safety